Uso da lousa digital interativa por professores na educação infantil: limites e possibilidades - Juliana de Almeida Fortunato (2021)
The present research has as general objective to understand the use of LDI by Early Childhood Education teachers in their pedagogical practices and to reflect on how the resources and possibilities of using LDI can contribute to the teaching practice in the teaching and learning process of children in Education Childish. Therefore, initially, the target audience was composed of teachers from Municipal Early Childhood Education Units in the municipality of Santa Luzia, in Minas Gerais. Subsequently, teachers of Early Childhood Education from other regions of the same state. Pursuing to achieve the specific objectives of presenting the LDI as well as its limits and possibilities of use, in Early Childhood Education, and to reflect on the continuing education of teachers and the use of digital technologies as pedagogical didactic instruments to support education, it was prepared, in the Virtual Learning Environment (Moodle) and offered to the target audience in two offers, the LDI course, which totaled 255 subscribers. The course made it possible to identify propelling and restrictive aspects regarding the use of LDI among teachers participating in Early Childhood Education. Defined as an action research, with a predominantly qualitative methodological approach, of an exploratory nature, the research has subsidies of a quantitative nature. In order to support its theoretical framework, discussions about ICT were supported by Behar (2018, 2020), Silva (2013), Ferrari (2012) and Kenski (2012), in the reflections on LDI, in Kalinke, Mocrosky Panossian and Banin (2017), Nakashima and Amaral (2010) and Gomes (2010). To deal with Early Childhood Education, we use studies carried out by Canaan, Ribeiro and Paola (2017), Vygotsky, Luria and Leontiev (2016), Couto (2013) and Baptista (2010). Regarding continuing education, as a contribution to teaching practice and the use of technologies in the classroom, it was based on the studies of Ferreira e Silva (2013), XAVIER (2013). Data collection and analysis were carried out through the application of online questionnaires where 90% of the participating teachers declared not to use the LDI; focus group where some points reported in the courses could be confirmed and; reflective analysis of the contents created by the participants in the virtual environment, which resulted in the educational resource Lousa Digital Interativa: contributions to Early Childhood Education with 13 suggestions for activities and websites for teachers and a brief presentation of LDI. With this research, we hope to contribute to the teaching practice of Early Childhood Education teachers and their training in the effective use of resources such as LDI for the rise of quality teaching and learning. We understand that the analysis carried out does not end here, since the demand for further study is necessary due to the various possibilities and results achieved with this research.